Koran Daerah di Bawah Bayang Penguasa dan Pengusaha: Kasus Kebijakan Kemitraan dalam Penerbitan Lombok Post - Ariadi, Lalu Gita (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
This study is aimed at understanding policy process at the local level, particularly with regards to the effectiveness of policy on kemitraan (lit. privatization), the potential advantages that would be obtained by the public as well as the private sector. Privatisation in local governance has a bright future for both sectors as it is also in line with current policy on regional autonomy. The findings of this research show that kemitraan policy has been run effectively at the local level and it could give social, political and economic advantages to the local government, the businessmen and the community at large. The government does not have to intervene in much of the societal fife and the private sector can cu-commodate the government interest without spoiling each other.